Changes in Ground Reaction Forces and Center of Pressure Parameters of Paws When Wearing Dog Boots in Dogs - Bieber, Bianca; Reicher, Bianca; Tichy, Alexander; Bockstahler, Barbara (Frontiers in Veterinary Science, 2022)
Dog boots are commonly used as protective footwear against snow, ice, hot sand, road salt, and paw injury. Only a few studies exist in veterinary medicine that capture the impact of dog boot replacements, such as bandages, on ground reaction forces (GRF) in dogs. To our knowledge, no studies have investigated the effect of dog boots on the center of pressure (COP) in dogs. This study investigated changes in the GRF of the whole limb and selected COP parameters of the paws while wearing dog boots in five Labrador Retrievers. After habituation, data were collected by walking and trotting dogs over a pressure platform without boots (control measurement) and under five different test conditions (wearing boots on all limbs, boots on both front limbs, boots on both hind limbs, one boot on the left front limb, and one boot on the right hind limb). The most prominent change was detectable when one boot was worn on the left front limb, with a decrease of peak vertical force (PFz %) in the left front limb at trot which led to a significant difference between both front limbs and a significant increase of PFz (%) in the right hind limb. Additionally, in both tempi, the vertical impulse (IFz %) showed significant differences between the front limbs; in trot, there was also an increase in the right front limb compared with the control. Furthermore, some significant changes in COP parameters were detected; for instance, all test conditions showed a significant increase in COP area (%) at the right front limb during walking compared to the control. Therefore, our results show that wearing the tested dog boots in different constellations seems to have an impact on GRF and some COP parameters.